PENGGUNAAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI POKOK GELOMBANG MEKANIK DI KELAS XII SMA NEGERI - Rozi Nasution, Sari Wahyuni; Zuliani, Unita Sukma (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
The aims of this research wa to know whether there was a significent influence of using experiment method on physics achievement in mechanic waves subject at the twelfth grade students of SMA Negeri 1 Pangaribuan. The approach of this research was experimental method. The population of this research was all the twelfth grade students of IPA majors SMA Negeri 1 Pangaribuan. They were consist of 3 classes which include 120 students. This research use cluster random sumpling technique to take sample, so the total sample 40 students. In collecting the data, the writer used test and questionnaire. The data was analyzed two ways. They are descriptive analysis and inferential statistic. Based on descriptive analysis, the average of using experiment method was 2.85. It was categorized “good”. Physics achievement in mechanic waves subject before using experiment methode had average 63.50, it was categorized “enough”. While physics achievement in mechanic waves subject after using experiment method had average 80.38, it was categorized “very good”. Based on inferential statistics, it could be gotten that tcaunt = 17,39 and ttable = 1,68 at confidence level 95% or error level 5%, df = N - 1 = 40 - 1 = 39. It could be seen that tcaunt was greater than ttable (17,39 1,68). The hypothesis was accepted. In the other words, there was a significant influence between using experiment method on physics achievement in mechanics waves subject at the twelfth grade students of SMA Negeri 1 Pangaribuan.